Capacity Planning in Non-uniform Depth Anchorages - ALKAYA, ALİ FUAT (SPRINGER-VERLAG BERLIN, 2015)
Commercial vessels utilize anchorages on a regular basis for various reasons such as waiting for loading/unloading, supply, and bad weather conditions. Recent increase in demand for anchorage areas has mandated a review of current anchorage planning strategies. In particular, current state-of-the-art anchorage planning algorithms assume that the anchorage areas are of uniform depth, which is quite unrealistic in general. In this study, we introduce an algorithmic modification to current anchorage planning methods that takes into account non-uniformity of anchorages. By exploiting the depth non-uniformity, our algorithm significantly improves the number of vessels that can be accommodated in an anchorage and it can easily be incorporated into existing anchorage capacity planning decision support systems.
Keywords: Maritime transportation; Anchorage; Optimization algorithm; Decision support system; OPEN DIMENSION PROBLEM